Gas hydrates, fluid venting and slope stability on the upper Amazon deep-sea fan - Praeg, D.; Silva, C; Reis, A, T; Ketzer, J-M; Migeon, S; Unnithan, Vikram; Perovano, Rodrigo, J; Cruz, Alberto; Gorini, Christian (CCSD, 2018)
International audience Gas hydrates are ice-like compounds of water and volatiles (mainly methane) that are stable in deep-sea sediments due to high pressures and low temperatures. Changes in oceanographic conditions that reduce their stability field (e.g. sea level lowering, bottom water warming) have been suggested to trigger continental slope failures. The Amazon deep-sea fan is a major Plio-Quaternary depocentre associated with large-scale slope instabilities, in which the presence of gas hydrates has been reported from a discontinuous bottom simulating reflection (BSR) on the upper slope. Reductions in gas hydrate stability during lowered sea levels have been argued to trigger megaslides from the upper fan; megaslides have also been linked to tectonism within an extension- compression system on the upper fan recording its collapse above deep detachments. Here we present the first systematic mapping of the Amazon fan BSR using a regional grid of 2D/3D seismic reflection data, and argue the results to provide evidence for stability zone changes driven from below by fluid upwelling. The BSR is seen to extend over an area of at least 6800 km2 as elongate patches up to 10s km wide and >100 km long that coincide with the crests of thrust-fold anticlines. The BSR patches lie within 300 m of seafloor, in places rising beneath seafloor features that 3D seismic imagery show to be pockmarks and mud volcanoes. The BSRs are shallower than the methane hydrate stability zone calculated using regional datasets, and inversion of depths to temperatures yields spatially variable gradients up to 10 times background values in well data from the fan. We interpret the elevated BSR patches to record the upwelling of warm, gas-rich fluids via the thrust-folds. We propose that changes in heat flux due to episodic fluid flow, notably during fault movements, will result in gas hydrate dissociation to reduce pore pressures at the base of the stability zone. This mechanism could account for recurrent large-scale failures from the ...